Comprehensive Assessment of Step Aerobics Exercises Effect on Women’s Physical Performance and Physical Health - Масляк, І. П. (Physical Education Theory and Methodology, 2015)
Objective: To identify the dynamics of physical performance and physical health indicators in young and middle-aged women under the effect of step aerobics exercises. Material and methods. The grounds for the study were Kharkiv fitness club “Zorianyi”. The participants were 28 women aged 20-35. The study used the following methods: theoretical analysis of scientific and methodical literature, pedagogical experiment, methods of mathematical statistics, methods of determining physical performance (Harvard step test) and physical health (anthropometry, pulsometry, tonometry, spirometry, dynamometry). Results: The study assessed the level of physical performance and physical health; analyzed age-related performance differences; determined the level of the effect of step aerobics on women’s physical performance and physical health. Conclusions: Step-aerobics exercises proved to have a positive effect on the level of physical performance and physical health of the young and middle-aged women.